An Examination of Rail Infrastructure Charges - Hylén, Bertil (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
This Report has been prepared for the European Commission by NERA, national economic research associates, (UK) in conjunction with Nomisma (IT); Statens väg- och transport-forskningsinstitut, VTI, (SE); Institut für Verkehrswesen, Eisenbahnbau und –betrieb, Universität Hannover, IVE, (DE); Ecole Nationale des Ponts et Chaussés, ENPC, (FR) and Business and Projects Management, BPM, (GR). The main objective of the Report is to provide input for a Community Code of Conduct on rail infrastructure charging. Its findings are based on both an examination of the current method (if any) of charging for rail infrastructure in each Member State, and a consideration of general issues related to the construction of charges, the structure of charges and the effect of the charging system. We would like to thank all those organisations and individuals who have co-operated with our research.